Comparing vegetation indexes between CBERS, Landsat and Rapideye images for the Brazilian Cerrado area (Revista Espinhaço, 2020)
This study aims to compare the quality of the NDVI and SAVI indices and their difference maps from images from the CBERS-4, Landsat-8 (lower resolution), and Rapideye-3A (higher resolution) satellites in an area of Cerrado, Minas Gerais, Brazil. First, the two indexes were calculated for the three images, then these maps were reclassified from the pixel range into four classes using the field and MAPBIOMAS project as the criteria. Following the maps of the CBERS-4 indices were compared with the Rapideye-3A correspondent. The same was done with landsat-8 maps. All processes were carried out with images from May 2015 in ArcGIS. CBERS reported results for NDVI similar to Rapideye, but SAVI presented errors. NDVI and SAVI results from Landsat image showed outliers when compared to CBERS and Rapideye data. The CBVI-4 NDVI difference maps indicated an approximation with the Rapideye results demonstrating the quality of the first, despite its lower resolution. The SAVI results were not satisfactory, either by error (CBERS-4) or due to very different values from the reference satellite, probably related to the use of a constant L unable to portray the variety of vegetation.
Keywords: NDVI and SAVI; Difference map; Remote Sensing